KAJIAN AWAL UNTUK MEMPERCEPAT PEMULIHAN KONDISI SOSOAL EKONOMI MASYARAKAT TERKENA BENCANA ERUPSI GUNUNG MERAPI MELALUI BUDIDAYA ULAT SUTERA - Robertus Sudaryanto; Supriyadi Supriyadi; Purwanto Purwanto (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2011)
Title : Initial Assessment to Accelerate Recovery of The Affected Community Social Economic Mount Merapi Eruption Through The Cultivation of Silkworms. Research purposes to obtain the suitability of land for mulberry (Morus sp) in the affected area  2010  eruption  of  Mount  Merapi,  in  Balerante  Kemalang  Klaten  in  Central  Java.  This information  is necessary to create activities that can accelerate  the recovery of socio‐economic conditions of society through silkworm farming. The method used is an inventory of soil and land characteristics   through   field   surveys.   Step   (1)   an   inventory   of  climatic   factors,   soil   and topography to make the Land Unit Map (SPT). Stage (2) analysis of soil fertility in the laboratory to complement the characteristics of land that has not been obtained at the time of field survey. Stage (3) develop / describe the characteristics  of the land on each Land Unit on our soil. Stage (4) The process of evaluating the suitability of the land, the match (matching) characteristics  of land with mulberry plant growth requirements. The results of our actual and potential land suitability. This map is useful to provide guidance on the cultivation of mulberry plants. (Morus sp.),  Results  showed  that  most  of  land  unit  in  this  area  has  a  fitness  class  S2nr  (Quite  in accordance with the limiting nutrient retention)Keywords:  actual and potential land suitability, land characteristics, referrals, and cultivation